Ole Høiris, Ole Marquard and Gitte Adler Reimer (eds.), Grønlændernes syn på Danmark. Historiske, kulturelle og sproglige perspektiver (Aarhus: Aarhus Universitets foreleg, 2019) - Jacob Dahl Rendtorff (Nordicum-Mediterraneum, 2020)
A review of the book: Ole Høiris, Ole Marquard and Gitte Adler Reimer (eds.), Grønlændernes syn på Danmark. Historiske, kulturelle og sproglige perspektiver [The Greenlander’s view of Denmark. Historical, Cultural and Language Perspectives](Aarhus: Aarhus Universitets foreleg, 2019) A review of the book: Ole Høiris, Ole Marquard and Gitte Adler Reimer (eds.), Greens’ views on Denmark. Historical, cultural and linguistic perspectives [The Greenlander’s view of Denmark. Historical, Cultural and Language Perspectives] (Aarhus: Aarhus University Foreleg, 2019)